Taxonomic status of Anolis baccatus Bocourt 1873 (Reptilia, Squamata, Polychrotidae) - Köhler, Gunther (Zootaxa, 2011)
The examination of the holotype of Anolis baccatus Bocourt 1873 revealed that it is a representative of A. carolinensis Voigt 1832 and, therefore, this name is synonymized with the latter epithet.